One Man's Quest for the State of Software Engineering's Practice. - Glass, Robert L. (Communications of the ACM, 2007)
The article analyzes researchers' findings of software practitioners' activities in an attempt to determine the state of practice in the software engineering profession. While it is easy to determine the state of the art, there are few sources that discuss the state of the practice, specifically what software practitioners actually do. The author examines data from surveys of software practitioners' activities to determine exactly what software practitioners do day-to-day and how they do it.